1278 The role of placenta in infant body composition; can the placenta predict infant body composition?. (17th August 2022) - Lucas, Nishani; Fonseka, Omalka; Senarath, Upul; Lanerolle, Pulani; Hills, Andrew; Wickramasinghe, Pujitha
Abstract : Aims: To assess the relationship between placental size and infant body composition, maternal characteristics and cord leptin, adiponectin, IGF-1 and insulin Methods: This is part of a descriptive longitudinal study, 2015-2019, at Professorial Unit, De Soysa Hospital for Women, Colombo, Sri Lanka. Body composition [fat mass (FM) and fat free mass (FFM)] was measured at 3, 6, 9, 12, 18 and 24 months based on the deuterium-dilution-method using saliva sample analysis, in healthy, term, singleton babies born to non-smoking mothers, >18years of age who agreed to attend follow up monthly and 2-monthly for the first and second years. Placental weight, maximum diameter and maximum thickness was measured using SECA 334 infant scale to the nearest 5g and metal ruler to the nearest 0.1cm. Maternal weight at booking visit was obtained from the maternal health record whereas maternal height was measured using SECA 271 stadiometer. Umbilical cord blood was tested for leptin, insulin, adiponectin and insulin using ELISA technique. Ethics approval was obtained from Faculty of Medicine, University of Colombo. Data was analysed via SPSS v27 using independent samples T test, Pearson correlation and Multiple hierarchical regression, to determine whether placental parameters can predict body composition of infants, after ensuring that assumptions of normality, linearity, multicollinearity and homoscedasticity were met. Simple linear regression was used to look at the relationship ot infant body composition and placental characteristics with maternal anthropometry and cord blood. Results: A total of 236 placentas were examined. Mean and SD of placental weight, maximum diameter and thickness were 540±111g, 18.5±2.6cm and 2.2±0.6cm respectively. There was no significant difference in the weight (526g vs 550g, p=0.1), diameter (18.3 vs 18.6cm, p=0.5) and thickness (2.3vs2.2 cm, p=0.5) of the placenta in girls and boys respectively. SGA babies' placentas had significantly lesser weight (440gvs554g, p<0.001) and diameter (16.8 vs 18.8cm, p<0.001) with increased thickness (2.3vs2.2cm, p=0.627) compared to non-SGA babies. Placental thickness was the strongest contributor for FM, accounting for a variability of 5.1% at 3 months [beta=0.244, p=0.029, r2change=0.11, F(3, 84)=3.602, p=0.017] and 10.8% at 18 months(beta=0.352, p=0.37, r2change=0.18, F(3, 29)=2.65, p=0.044) as well as the strongest contributor for FFM accounting for a variability of 14.5% at 18 months[beta=0.409, p=0.016, r2change=0.198, F(3, 29)=2.983, p=0.033]and 31.7% at 24 months[beta=0.602, p<0.001, r2change=0365, p=0.009] compared to placental weight and diameter after controlling for maternal age, pregestational weight and BMI. Fat% increased by 4% and FFMI decreased by 1 for each cm of placental thickness. Each 1 kg increase of maternal weight at booking visit increased infant FM by 7g [beta=0.007, p=0.02, r2 =0.043, p=0.02], fat mass index by 20g/cm [beta=0.023, p=0.023, r2=0.046, p=0.02] and placental weight by 1g [beta=0.001, p=0.022, r2=0.027, p=0.022]. Each 1cm increase in placental thickness increased umbilical cord leptin levels by 0.076ng/ml [beta=0.076, p<0.001, r2=0.102, p<0.001]. Conclusion: Increased infant fat mass was associated with increased maternal weight at booking visit and increased placental thickness, where increased placental thickness was associated with increased cord blood leptin levels. This implies that maternal anthropometry may mediate offspring adiposity through changes in cord leptin levels and increase in placental thickness. Placenta can be used to predict body composition in infants.